Pengaruh Pola Makan Vegetarian Lakto-Ovo terhadap pH Saliva - Shanty Chairani; Vivi Stefani; Nursiah Nasution (Andalas Dental Journal, 2023)
Background: Lacto-ovo vegetarian has been associated with a higher risk of nutritional deficiencies. Some studies have reported that nutritional deficiencies could affect salivary pH. Objective: The purpose of this study was to determine the effect of a lacto-ovo vegetarian diet on salivary pH differences. Method: This study used an observational analytic study with a cross sectional approach. This study involved 40 healthy subjects aged 17-44 years consisting of 2 groups: lacto-ovo vegetarian (n= 20) for at least 1 year and non vegetarian (n = 20) as a control group. Pregnant women, anticholinergic and alcohol consumption, smoking habits and DMFT > 5 are exclude from this study. The collection of unstimulated saliva was done using the spitting method. Saliva pH was measured using a digital pH meter. The data obtained were statistically tested using the Mann-Whitney test. Results: The mean salivary pH values in the lacto-ovo vegetarian diet group were lower than those of the non vegetarian group. There is a significant difference in salivary pH between lacto-ovo and non vegetarian group (p<0,05). Conclusion: Individuals with lacto-ovo vegetarian diet have a low salivary pH which might influence their oral health.